Effect of Dentifrices with Different Abrasives on the Surface Roughness of a Nano Composite Resins materials (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: to evaluate the effect of different dentifrices on the surface roughness of two composite resins(nanofilled-based and nanoceramic – based composite resins). Materials and methods: Forty specimens(diameter 12 mm and height of 2mm) prepared from different composite resin materials: Z350 (nanofilledcomposite, and Ceram-X (nanoceramic) .they were subjected to brushing simulation equivalent to theperiod of 1 year. The groups assessed were a control group brushed with distilled water (G1), Opalescencewhitening toothpasteR (G2), Colgate sensitive pro-relief (G3) and Biomed Charcoal Toothpaste (G4). Theinitial and final roughness of each group was tested by surface roughness tester. The results were statisticallyanalyzed using ANOVA and Tueky test at 0.05 significance level. Results: the surface roughness of thetwo tested composites brushed with the tested dentifrices was statistically higher than the roughness foundin control group. Comparison among the three types of dentifrices showed that there was a statisticallyhigh significant difference in the surface roughness among all subgroups. Charcoal Toothpaste showed thehighest surface roughness increase. Conclusion: Whitening dentifrices increase the surface roughness ofdental composite thereby compromising its durability. Changes in composite depended on the material itselfand the dentifrices used.